2022
DOI: 10.1002/lary.30073
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electronic (E)‐cigarette Vapor and Cigarette Smoke in Cultured Vocal Fold Fibroblasts

Abstract: Objective: The public use of electronic-cigarettes (e-cigs) is rapidly growing. When heated, e-cigs produce a vapor that is inhaled. The vocal folds are among the first tissues exposed to this insult. However, the impact of e-cigs on vocal fold health is almost entirely unknown. Our objective was to evaluate the effects of e-cig vapor on cultured human vocal fold fibroblasts (hVFFs), the primary cell type of the lamina propria. We compared the cellular effects of e-cig vapor without and with nicotine and conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 56 publications
(166 reference statements)
0
19
0
Order By: Relevance
“…11 E-cigarette extract also reduced human VF fibroblast viability to a cytotoxic level. 12 Preliminary in vivo studies have targeted mostly inflammatory responses in the laryngeal mucosa of rodents following e-cigarette exposure. A 1-month exposure in rats revealed no significant changes in epithelial distribution and inflammation, 13 while 4 months of exposure in mice induced elevated levels of the inflammatory cytokine, IL-4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 E-cigarette extract also reduced human VF fibroblast viability to a cytotoxic level. 12 Preliminary in vivo studies have targeted mostly inflammatory responses in the laryngeal mucosa of rodents following e-cigarette exposure. A 1-month exposure in rats revealed no significant changes in epithelial distribution and inflammation, 13 while 4 months of exposure in mice induced elevated levels of the inflammatory cytokine, IL-4.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure of human‐engineered vocal fold (VF) mucosa to e‐cigarette extract in vitro disrupted innate immune responses and induced epithelial remodeling 11 . E‐cigarette extract also reduced human VF fibroblast viability to a cytotoxic level 12 . Preliminary in vivo studies have targeted mostly inflammatory responses in the laryngeal mucosa of rodents following e‐cigarette exposure.…”
Section: Introductionmentioning
confidence: 99%
“…16,18,25,28,30,35,40,[42][43][44][45][46]49,53,62 Genotoxicity was seen primarily in the oral cavity, but also in the oropharynx and larynx, and was detected by increased DNA fragmentation, adducts, double-or single-strand breaks, appearance of micronuclei or metanuclear abnormalities, or increased expression of genes or proteins involved with DNA damage or repair pathways. 14,19,[22][23][24][25]27,32,51 Histological changes associated with acute and subchronic e-cigarette aerosol exposure in animal models were seen in the oral cavity, submandibular gland, nasal cavity, larynx, and trachea; however, the majority of these changes were considered adaptive and resolved following a recovery period. 30,31,37,47,50,52,[56][57][58][59]61,64 Persistent histological changes in the nasal cavity and larynx included: mild epithelial hyperplasia and squamous metaplasia, and mucus hypersecretion.…”
Section: Resultsmentioning
confidence: 99%
“… 172 , 173 In the larynx, rats exposed to e‐cig aerosols showed early evidence of hyperplasia and metaplasia of the mucosa, 174 although the results were not statistically significant in this limited study, and increases in IL‐4. 175 In addition, both nicotine‐containing and nicotine‐free e‐juice have been found to cause biologic disruptions including oxidative stress, DNA breakage, metanuclear anomalies, liposomal dysfunction, and solvent and lipid accumulation, and cytotoxicity in human gingival fibroblasts, 67 , 176 , 177 , 178 , 179 , 180 vocal fold epithelial cells and fibroblasts, 181 , 182 head and neck squamous cell carcinoma cell lines, 67 , 183 , 184 , 185 noncancerous oral and oropharyngeal epithelial cells, 139 , 178 , 186 , 187 , 188 , 189 , 190 , 191 , 192 middle ear epithelial cells, 193 , 194 , 195 nasal epithelial cells, 196 , 197 and organotypic cultures/organoids. 178 , 182 , 197 Interestingly, a recent study found that oral cancer cells exposed to e‐cig aerosols increased cell resistance to cisplatin through changes in drug transporters, suggesting a mechanism for e‐cig‐induced chemotherapy resistance.…”
Section: Discussionmentioning
confidence: 99%